Expression analysis of fecundity related genes in FecB carrier and non-carrier ewes by semi-quantitative PCR - Jigyasa Aggarwal; P. Ghalsasi; C. Nimbkar; B.K. Joshi; B.P. Mishra (Journal of Livestock Biodiversity, 2025)
In the present study, an attempt has been made to analyze the expression of genes associated with fecundity in FecB carrier and non-carrier ewes using semi-quantitative PCR. Ovary tissues were collected from one Garole (homozygous for FecB), one non-carrier Deccani and one heterozygous crossbred (Garole x Deccani) ewe with known litter sizes. Total RNA was extracted and reverse transcribed to generate cDNA. Expression of eight genes, likely to be associated with the regulation of ovulation rate, viz., BMPRIB, BMP15, STAT5, SMAD5, SMAD9, FSHR, LHCGR and GDF9 was analyzed by semi quantitative RT-PCR. Six genes, viz., BMPRIB, BMP15 STAT5, SMAD5, LHCGR and GDF9 showed differential level of expression across ewes of different breeds and FecB genotypes having different litter sizes. The expression of BMPRIB, SMAD5 and LHCGR was found to be higher in ewes homozygous for FecB mutation while the mRNA level of SMAD9 and FSHR was found to be similar across all the three genotypes. This preliminary study thus shows differential expression of investigated genes in FecB carrier and non-carrier ewes, which would further guide to analyze specific gene(s) quantitatively across specific physiological stages and in genotypes to elucidate their probable role in litter size